The punishment of heresy in Languedoc during the mid thirteenth century - Barmby, Harry (2017)
During the thirteenth century a number of papal inquests were held across Languedoc with the purpose of uncovering and suppressing support for heresy. One key aspect of these inquests was the sentencing of guilty deponents. Papal inquisitors employed a variety of penances to punish those found guilty of supporting two heresies: Catharism and Waldensianism. Such penances included pilgrimage, wearing crosses, financial penalties and imprisonment. The most obstinate heretics were handed over to the secular authorities for execution, or if deceased, exhumed and burned. In historiographical debates, discussion about penances has often been overlooked in favour of focusing on the procedure which preceded the sentencing. However, by examining inquisitors’ decision-making and the penances which they imposed, new light may be shed upon matters such as inquisitors’ attitudes towards punishment, the development of the post-interrogation procedure, and the relationships between inquests.